A new Munidopsis species (Galatheoidea, Munidopsidae) from the Southwestern Atlantic - Cardoso, Irene A.; Serejo, Cristiana S.; Rodrigues, Celso; Rodrigues, Celso (Zootaxa, 2014)
Six Munidopsis species are recorded to the Southwestern Atlantic: M. barbarae; M. erinacea; M. nitida; M. sigsbei; M. riveroi and M. transtridens. Herein a new Munidopsis species from Southwestern Atlantic is described: Munidopsis trindadensis sp.nov., was sampled off Trindade Island (Espírito Santo, Brazil) at 360 m depth and differs from all six species previously recorded in this region by the telson with seven plates.